BASLAWÍSH KLASSLARDA INGLIZ TILI PÁNIN OQÍTÍWDA ZAMANAGÓY PEDAGOGIKALÍQ TEXNOLOGIYALARDAN NÁTIYJELI PAYDALANÍW - Rambergenov, R.G. (SCIENCE and SOCIETY, 2024)
The article provides opinions and recommendations on the importance of using pedagogical technologies in teaching English in primary schools of secondary schools.